Pelican economic history of britain - Hill, Christopher (New York, 1980)
SOME of the subjects discussed in this book have already been created in my Century of Revolution, 1603-1714 (Vol. 5 of the Nelson History of England, 1961). Where possible I have used different illustrative material. Spelling and punctuation have been modernized in all quotations. The Index may help readers to identify persons referred to briefly in the text. Where a foot note refers to a book by the author's name only, or author's name and a date, the full title will be found in the Bibliography on pp. 289-91. It was not possible to document this book fully, but I have tried to acknowledge specific debts. I have drawn a great deal on the writings of others, particularly for Part Four. I am especially indebted to the work of Professor T. S. Ashton, Sir G. N. Clark, Dr Dorothy Marshall, Professor J. H. Plumb, Professor C. Wilson. I have also benefited by discussions with Dr K. R. Andrews and Mr A. L. Merson, and from hearing Professor Plumb's Ford Lectures in Oxford in 1965. Dr Eric Hobsbawm very kindly read part of the typescript, and Mr Edward Thompson the whole of it; both made many useful suggestions. Mr Paul Slack undertook the dreary task of reading the proofs and saved me from many mistakes. None of these, however, is to blame for the errors which remain. Nor is my wife, who read it all and helped at every stage in every way.
Keywords: Economic history - Great Britain